WORKSHOP KEWIRAUSAHAAN SEBAGAI UPAYA PENCIPTAAN WIRAUSAHA MUDA PADA REMAJA DI KOTA MALANG - Armanu Armanu; Ana Shofia Aryati; Khalilah Daud Isaac Makhmut (LPPM (Institute for Research and Community Services) Universitas Andalas Padang, 2024)
Indonesia, as a developing country with the fourth largest population in the world, faces significant challenges related to human resource quality and a high unemployment rate. The high unemployment rate is primarily due to the limited job opportunities available for the productive workforce. To address this issue, one solution offered is the development of entrepreneurship, especially for the younger generation. The purpose of this activity is to provide entrepreneurship training to 25 youth in Malang City, aiming to raise awareness of the importance of entrepreneurship and equip them with the basic skills needed to start a business. The method used in this activity is practice-based entrepreneurship training, where participants learn fundamental concepts of entrepreneurship, business planning, financial management, marketing, and innovation. Participants also have the opportunity to interact directly with experienced speakers and participate in business simulations. The results of this activity show that the training successfully increased participants’ motivation and knowledge about entrepreneurship. Participants demonstrated high enthusiasm in discussions and entrepreneurial exercises and actively responded to the material presented. In conclusion, this training program is effective in motivating youth in Malang City to embrace an entrepreneurial spirit, which ultimately has the potential to help them create their own job opportunities and contribute to the local economy. This program should be continued and optimized through collaboration with various parties to create a supportive ecosystem for developing innovative and competitive young entrepreneurs.